Cetuximab in Refractory Skin Cancer Treatment - Kalapurakal, Sini J (Ivyspring International Publisher, 2012)
Objectives: Non-melanoma skin cancer is the most common malignancy in US, with an annual incidence of in excess of 1.5 million cases. In the majority of cases, locoregional treatment is curative and systemic therapy is not indicated. Platinum-based chemotherapy regimens have been used most commonly in refractory cases. The use of cetuximab, a monoclonal antibody targeting epidermal growth factor receptor [EGFR], has been reported for skin cancer treatment. This current study evaluated eight cases of locally advanced and refractory basal cell or squamous cell cancers which were treated with cetuximab. Methods: This is a retrospective study on eight patients who had received cetuximab for treatment of cutaneous carcinoma since 2007 at Southern Illinois University School of Medicine (SIU-SOM) Medical Oncology clinic. Results: Three of the four patients with basal cell carcinoma and two of the four patients with squamous cell carcinoma maintained remission on treatment.. The main side effect was acneiform rash which required termination of treatment for one patient and dose reduction in another. Conclusion: The study indicates that cetuximab may have a beneficial role for patients with non-melanoma cutaneous carcinomas that are refractory to standard therapy.